Implementation of Al-Qur'an Reading Learning Tartili Method in MAS Sinar Serdang Perbaungan - Tira Rahayu; Haidar Daulay; Zulheddi Zulheddi (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This research aims to implement learning to read and write al-quran's tartili method in MAS Sinar Serdang Perbaungan as well as to improve student achievement in reading the Qur'an from those who are unable to read to be able to read well, correctly and fluently in tartil. From those who do not know the letters to know the letters of Tajweed and the Qur'anic punctuation properly. This program is carried out after midday prayers in congregation. To determine students' ability to read and write letters of the Qur'an, observations, interviews and documentation were carried out in the implementation, planning and evaluation of students in reading and writing the Qur'an in a tartili manner. In order to know the students' abilities in reading and writing, the teacher tests students with tests one by one. The research method used is the method of data reduction, data presentation, and drawing conclusions. To check the validity of the data, it is carried out perseverance of observation, tringuation and discussion of colleagues so that the data is more accurate. As well as field testing in class until the final test by writing.The results of this research find out how many students are able and unable to read and write. And creating students become clerics and clerics to be useful in the community environment.